Trust in safe public e-services: Translating policies into use. - Irene Bernhard; Elin Wihlborg (European Regional Science Association (ERSA), 2010)
The emerging information society changes the relations between public agencies and citizens in many ways. One of the most used is the use of public e-services for interactions between public agencies and citizens. Public e-services as such are innovations, even if the service as such has been there before, it is a new way producing and organizing the service. For successful implementation of innovations the innovations has to be considered as legitimate by all involved actors. They have to trust the organization and not at least its safety aspects. Safety in web-innovations is created through both the practical real technical arrangement and practical experiences of the use of the innovation. On a European and national level there are some policies and some standardization of public e-services. But since the Swedish public administrations rely on a double steering approach with strong constitutional regional and local autonomy such policies cannot be forced out into regional local public agencies. Instead such European and national statements become soft policy instruments in the local context and the implications from them rely on the local context and not at least the competences of the professionals in the administration. Since this is a new field of innovative practice it will build on an inductive methodological approach. The empirical work is primarily conducted through qualitative methods. The material will be of two types. Firstly, we will analyze general policy documents and specific policies from a selection of regional and municipal agencies. Secondly, we will analyze the constructions of meanings promoting safety on the web pages and in other information material promoting citizens to use e-services. What benefits are highlighted and how are risks and safety presented and motivated? Thereby we will be able to contribute to the communication and mediation of safety and promotion of innovation and efficiency in public administration. This analysis will both contribute to the discussion of safety in public e-services and the importance of organizational arrangements. It may also end in an innovative discussion of the interplay of standardization and local autonomy.
Keywords: 330